Mature Larval Dispersal and Adult Emergence of the Economically Significant Pest, Scirtothrips aurantii Faure (Thysanoptera: Thripidae), in Commercial Citrus. Issue 2 (23rd March 2018) - Gilbert, Martin J; Samways, Michael J
Abstract: Scirtothrips aurantii Faure (Thysanoptera: Thripidae) is a major pest of citrus fruit in subtropical southern Africa. Population monitoring is an important aspect of S. aurantii control, but additional information is required on its phenology. Dispersal of mature larvae onto the soil surface from the tree canopy, and emergence of adults, were assessed using dispersal/emergence (D/E) traps in an untreated citrus orchard in South Africa. Overall, 90.7% of adult Thysanoptera emerging from soil / leaf litter beneath the citrus trees were S. aurantii, of which 35.7% were males, and 64.3% were females. Female S. aurantii having survived winter as adults oviposited on the early spring flush. This resulted in the first population peak of larvae dropping to the ground to pupate and adults emerging in spring, September to early October, as the first vegetative flush of the citrus-growing season hardened, and fruit was set as blossoming ended. Initial infestation of young fruit occurred after a build-up of larval numbers on the soft citrus flush late July to early August. The second generation larval and adult peak occurred late November to early December, whether there was new flush or not, as young fruit could support the S. aurantii population. A third peak occurred mid-December to late January, depending on year. Thus, there were three generations of S. aurantii during the period of citrus fruit susceptibility to thrips damage (September–January). After the autumn flush in April, another peak of larvae and adults occurred before the population declined to a minimum from May to July.